2008
DOI: 10.1111/j.1600-0625.2008.00739.x
|View full text |Cite
|
Sign up to set email alerts
|

Heparanase 1: a key participant of inner root sheath differentiation program and hair follicle homeostasis

Abstract: Heparanase is a heparan sulphate endo-glycosidase which was previously detected in the outer root sheath of murine hair follicles. Heparanase overexpression was reported to improve mouse hair (re)growth. In this study, we investigated its involvement in human hair biology. Immunofluorescence detection was used to explore heparanase distribution in both anagen and catagen hair follicles. Heparanase functionality was assessed in in vitro cultured hair follicles, in the presence of a heparanase activity inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…Our findings are in accordance with the absence of HS impeding progression into catagen. Moreover, Malgouries et al (29) showed previously that there is an increase in heparanase expression in human anagen hair follicles; however, at the onset of catagen, hair follicle heparanase expression ceases, further supporting our findings. Therefore, our results clearly reveal the importance of fluctuations in the HS levels of hair follicle epithelial cells, which dictate hair follicle cycling and thus play a vital role in hair follicle homeostasis.…”
Section: Interestingly Ext1supporting
confidence: 91%
See 1 more Smart Citation
“…Our findings are in accordance with the absence of HS impeding progression into catagen. Moreover, Malgouries et al (29) showed previously that there is an increase in heparanase expression in human anagen hair follicles; however, at the onset of catagen, hair follicle heparanase expression ceases, further supporting our findings. Therefore, our results clearly reveal the importance of fluctuations in the HS levels of hair follicle epithelial cells, which dictate hair follicle cycling and thus play a vital role in hair follicle homeostasis.…”
Section: Interestingly Ext1supporting
confidence: 91%
“…Previous studies have shown that heparanase expression varies throughout hair follicle cycling with increased expression in anagen hair follicles and decreased expression in catagen follicles (28). Moreover, the overexpression of heparanase accelerates the rate of anagen, and the authors speculate that the release of growth factors upon heparanase cleavage would play a major role (29). Herein we show that it is the absence of HS within the hair follicle that triggers the enhanced rate of anagen and not the release of growth factors upon heparanase digestion.…”
mentioning
confidence: 94%
“…In normal tissue, heparanase is expressed in placenta, keratinocytes and platelets, but not in connective tissue cells [28][29][30][31]. In normal skin, heparanase is expressed in stratum corneum and hair inner root sheath, and may be involved in differentiation, desquamation and hair growth [30,31].…”
mentioning
confidence: 99%
“…Furthermore, heparanase expression is not restricted to pathological conditions and the activity has been found in hair follicle [26, 27] and in the skin [28]. Heparanase was detected in the outer root sheath of murine hair follicle [26], while it mainly expressed in the inner root sheath of human hair follicle [27], suggesting, despite of differential expression between the species, that heparanase may be a key factor in differentiation of a follicular stem cell and hair homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Heparanase was detected in the outer root sheath of murine hair follicle [26], while it mainly expressed in the inner root sheath of human hair follicle [27], suggesting, despite of differential expression between the species, that heparanase may be a key factor in differentiation of a follicular stem cell and hair homeostasis. In human epidermis, heparanase expression has been reported to be closely related to keratinocyte differentiation and was mainly found in the stratum granulosum [28].…”
Section: Discussionmentioning
confidence: 99%